Involvement of the Choroid Plexus in the Pathogenesis of Niemann-Pick Disease Type C - Van Hoecke, Lien; Van Cauwenberghe, Caroline; Dominko, Kristina; Van Imschoot, Griet; Van Wonterghem, Elien; Castelein, Jonas; Xie, Junhua; Claeys, Wouter; Vandendriessche, Charysse; Kremer, Anna; Borghgraef, Peter; De Rycke, Riet; et al. (Frontiers in Cellular Neuroscience, 2021)
Niemann-Pick type C (NPC) disease, sometimes called childhood Alzheimer’s, is a rare neurovisceral lipid storage disease with progressive neurodegeneration leading to premature death. The disease is caused by loss-of-function mutations in the Npc1 or Npc2 gene which both result into lipid accumulation in the late endosomes and lysosomes. Since the disease presents with a broad heterogenous clinical spectrum, the involved disease mechanisms are still incompletely understood and this hampers finding an effective treatment. As NPC patients, who carry NPC1 mutations, have shown to share several pathological features with Alzheimer’s disease (AD) and we and others have previously shown that AD is associated with a dysfunctionality of the blood-cerebrospinal fluid (CSF) barrier located at choroid plexus, we investigated the functionality of this latter barrier in NPC1 pathology. Using NPC1-/- mice, we show that despite an increase in inflammatory gene expression in choroid plexus epithelial (CPE) cells, the blood-CSF barrier integrity is not dramatically affected. Interestingly, we did observe a massive increase in autophagosomes in CPE cells and enlarged extracellular vesicles (EVs) in CSF upon NPC1 pathology. Additionally, we revealed that these EVs exert toxic effects on brain tissue, in vitro as well as in vivo. Moreover, we observed that the disease-derived CSF EVs are able to induce typical brain pathology characteristics of NPC1-/-, more specifically microgliosis and astrogliosis. Taken together, our data reveal for the first time that the choroid plexus and CSF EVs might play a role in the brain-related pathogenesis of NPC1.